2010
DOI: 10.1007/s10826-010-9435-y
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Inhibition and Attentional Control in Adolescents: Robust Relationships with Anxiety and Depression

Abstract: Behavioral inhibition (BI) has been associated with the development of internalizing disorders in children and adolescents. It has further been shown that attentional control (AC) is negatively associated with internalizing problems. The combination of high BI and low AC may particularly lead to elevated symptomatology of internalizing behavior. This study broadens existing knowledge by investigating the additive and interacting effects of BI and AC on the various DSM-IV based internalizing dimensions. A sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 33 publications
4
38
1
1
Order By: Relevance
“…For example, effortful control is the ability to self-regulate emotions, attention and behavior. Internalizing problems are associated with low effortful control (Eisenberg et al, 2001;Sportel, Nauta, de Hullu, de Jong, & Hartman, 2011). High effortful control has been related to more active coping and lower adjustment problems later in development (Lengua & Long, 2002;Nigg, 2006;Rothbart, 2011).…”
Section: Child Temperament and Childhood Anxietymentioning
confidence: 99%
“…For example, effortful control is the ability to self-regulate emotions, attention and behavior. Internalizing problems are associated with low effortful control (Eisenberg et al, 2001;Sportel, Nauta, de Hullu, de Jong, & Hartman, 2011). High effortful control has been related to more active coping and lower adjustment problems later in development (Lengua & Long, 2002;Nigg, 2006;Rothbart, 2011).…”
Section: Child Temperament and Childhood Anxietymentioning
confidence: 99%
“…The factor of greatest interest in the present investigation was that of effortful control, and this factor is made up of subscales that measure attentional control (ability to appropriately focus or shift attention), inhibitory control (ability to suppress inappropriate behavior), and activation control (being able to perform an action despite wanting to avoid it). Previous research has shown strong evidence of the internal consistency reliability and convergent validity of ATQ factors and subscales (Evans & Rothbart, 2007), and the measure has been used successfully in previous adolescent samples (e.g., Sportel et al, 2011). …”
mentioning
confidence: 99%
“…They found that effortful control was negatively related to externalizing problem behaviors at all three time periods. In a study that measured both BIS/BAS and attentional control in a non-clinical sample of 1,806 adolescents, Sportel, Nauta, de Hullu, de Jong, and Hartman (2011) found that high levels of behavioral inhibition and low levels of attentional control combined to predict higher levels of internalizing problems, with behavioral inhibition being more strongly associated with anxiety symptoms, while low attentional control was more strongly related to depressive symptoms. Taken together, findings of these studies highlight the importance of effortful control and its sub-constructs as predictors of adolescent psychopathology.…”
mentioning
confidence: 99%
“…Although previous studies have found support for a meditational role for AC in the relationship between pre-existing risk factors and adverse outcomes (Sportel, Nauta, de Hullu, de Jong, & Hartman, 2011;Yap et al, 2011), a second limitation of our study is that the mediator (or moderator) was measured at the same time point as the predictor variable. This design constraint precludes establishing temporal precedence of either trait-anxiety or AC in our model.…”
Section: Discussionmentioning
confidence: 83%